Boron-boron dehydrocoupling of boranes initiated by reaction with iodine - Elias, Jana; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2019)
A new boron-boron dehydrocoupling strategy was established, providing convenient access to some diborane(4) compounds starting from simple borane adducts under mild conditions. In contrast to the traditional pathway using a reducing reagent, the reduction from BIII to BII was paradoxically initiated by the addition of the oxidation-reagent iodine. A reaction pathway for this unusual reaction was proposed based on quantum-chemical calculations.